Genetically modified animal models and Osteoimmunology - DOUNI (Ε.ΝΤΟΥΝΗ) E. (Journal of the Hellenic Veterinary Medical Society, 2017)
The completion of the human and mouse genome DNA sequences easily enabled chromosomal localization for each gene, whereas the role of each gene remains largely unknown. Functional Genomics constitutes the new area of Molecular Biology that aims to identify the function(s) of each gene in order to understand the pathogenic mechanisms in various human diseases. The mouse has been extensively used more than any other animal organism in biomedical research, because, except for the similarities it displays with humans, its genome can be genetically modified rather easily. During the last two decades, technological advances enable almost all kinds of mutations in the mouse genome. More specifically, the study of genetically modified mice revealed the continuous interaction between various systems within the organism, such as the interplay between the skeletal and the immune system, introducing the interdisciplinary area of Osteoimmunology. The cytokine RANKL constitutes the key molecule in Osteoimmunology, by regulating osteoclastogenesis, while deregulation of RANKL expression leads to diseases such as osteopetrosis or osteoporosis. In our laboratory we have recently generated, using state-of-the-art technologies, unique mouse models of RANKL-induced osteopetrosis or osteoporosis. These mouse models constitute excellent systems for the study of underlying pathogenic mechanisms and for the evaluation of novel therapeutic approaches at the preclinical level.